Quality Attributes for UX Design and Evaluation - et.al, Azham Hussain (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paperutilizeda literature survey method to find out the quality attributes (or design factors) that impact on or contribute to user experience in extant literature. The results indicate that there areten dimensions that model UX.Each of these dimensions has associated quality attributes that contribute to it and influence the UX of interactive applications. The study therefore proposes the use of these dimensions and the related quality attributes in the development and modeling of the UX of interactive systems. Furthermore, these dimensions and attributes can be utilized in the design and evaluation of interactive digital artifacts.